A Theoretical Framework for Modeling the Chemomechanical Behavior of Unsaturated Soils. Issue 9 (19th September 2014) - Wei, Changfu
Abstract : A theoretical framework is presented for modeling the chemomechanical behavior of multiphase porous media, in general, and unsaturated soils, in particular, which can address skeletal deformation, fluid flow, heat conduction, solute diffusion, chemical reaction, and phase transition in a consistent and systematic way. A general expression is derived for the electrochemical potential of a fluid species with explicitly accounting for the effects of osmosis, capillarity, and adsorption. The equilibrium behavior of porous media is investigated, and the composition of pore water pressure is identified. Explicit formulations are developed for the effective stress and intergranular stress, with consideration of physicochemical effects. It is shown that the negative water pressure measured by a conventional transducer can be significantly different than the true pore water pressure. It is also theoretically revealed that, other than the soil water characteristic function, a new pressure (or potential) function accounting for the physicochemical effects is generally required in analyzing the coupled chemomechanical processes in unsaturated soils. The new theory is capable of effectively explaining many salient phenomena occurring in water‐saturated porous media with a degree of saturation varying from an extremely low value to 100%, including Donnan osmosis, capillary fringe, air entry value, initial hydraulic head during seepage, and pressure solution. The new theory can be used to analyze the multiple coupled physical and chemical processes in the vadose zone.